Projecting the response of carbon sink potential to land use/land cover change in ecologically fragile regions - Wang, Ye; Liu, Jie; Zhang, Lirong; Xue, Zhongcai; Yang, Yue (Frontiers in Environmental Science, 2024)
The carbon storage service of the ecosystem in ecologically fragile areas is highly sensitive to regional land use/land cover (LULC) changes. Predicting changes in regional carbon storage under different LULC scenarios is of great significance for land use management decisions and exploring carbon sink potential. Therefore, taking the typical ecologically fragile area of the Luan River Basin as an example, this study analyzed the impact of LULC changes on carbon storage. The PLUS-InVEST model was employed to simulate LULC patterns for the year 2030 under three scenarios: natural development, cropland protection and urban development, and ecological protection. The study predicted the future carbon sink potential of the basin. Key conclusions include: 1) From 2000 to 2020, carbon storage exhibited a trend of decrease followed by an increase. In 2030, compared to 2020, carbon storage was projected to increase by 16.97% under the ecological protection scenario and decrease by 22.14% under the cropland protection and urban development scenario. 2) The increase in carbon storage was primarily attributed to the conversion of cropland and grassland to forestland, while the decrease in carbon storage was mainly associated with the conversion of forestland to grassland and cropland, as well as the transformation of grassland to cropland and construction land. 3) In the potential LULC scenarios of 2030, certain regions within the basin exhibited unstable carbon sink potential, strongly influenced by LULC changes. These areas were predominantly characterized by artificially cultivated forests, shrubs, and agricultural land. Implementing appropriate forest management measures and optimizing agricultural land management practices were essential to enhance carbon sink potential in these regions. 4) Population density, annual average temperature, and DEM (Digital Elevation Model) were the dominant factors driving the spatial variation of carbon sink potential in the Luan River Basin. The research results can provide theoretical basis for the rational planning of land use and the enhancement of carbon sink potential in ecologically fragile regions.